Śrīmadvālmīkirāmāyaṇam. Sundarkāṇḍam = Śrīmat Vālmīkirāmāyaṇam. Suntarakāṇṭam: Tēvanākariyilum Tamil̲ilum mūlattuṭan - Vālmīki.; An̲antarāma Tīkṣitar (N. Subadra ; Can be had from Higginbothams, 1982)
Part of an extended narrative poem on the life and heroic exploits of Rāma, Hindu deity.
In Sanskrit (Devanagari and Tamil scripts); translation, commentary, and prefatory matter in Tamil.
Part of an extended narrative poem on the life and heroic exploits of Rāma, Hindu deity.
2